Meta-analysis of association between Insulin-like growth factor-2 gene polymorphisms and growth traits in rabbits - Bashiru, HΑ; Oseni, SO (Journal of the Hellenic Veterinary Medical Society, 2025)
The Insulin-like growth factor-2 (IGF-2) gene is a potential candidate for marker assisted selection in rabbits due to its crucial role in regulating growth. However, the relationship between polymorphic variants of this gene and growth performance traits of rabbits under different genetic models has not been established. Therefore, the objective of this study was to assess the association between IGF-2 gene polymorphisms and growth performance traits in rabbits using meta-analysis. A systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guideline to identify and select relevant studies for inclusion in the analysis. Data were extracted from nine reports and included in the final analysis. Six genetic models under the assumption of co-dominance (3 models), recessive (1 model), dominance (1 model) and over-dominance (1 model) were evaluated. SPSS software was used for the assessment of heterogeneity, effect size calculation using hedges g method for standardized mean differences (SMDs) and the assessment of publication bias, while sensitivity analysis was conducted using OpenMeta® Analyst software. High heterogeneity was observed across studies under all genetic models. In addition, there were significant associations (P<0.05) between of IGF-2 gene with growth performance traits of rabbits. A simple relationship between these genotypes for growth traits of rabbits could be stated as Del/Del > A/Del >A/A. The findings infer the superiority of the Del allele over the A allele (Del>A) for growth performance traits of rabbits. These findings implied that the IGF-2 gene could be a potential candidate gene for marker assisted selection of rabbits for improved growth performance.